Domestic outsourcing in the United States: A research agenda to assess trends and effects on job quality - Annette Bernhardt; Rosemary L. Batt; Susan N. Houseman; Eileen Appelbaum (W.E. Upjohn Institute for Employment Research, 2016)
The goal of this paper is to develop a comprehensive research agenda to analyze trends in domestic outsourcing in the United States - firms' use of contractors and independent contractors - and its effects on job quality and inequality. In the process, we review definitions of outsourcing, the available scant empirical research, and limitations of existing data sources. We also summarize theories that attempt to explain why firms contract out for certain functions and assess their predictions about likely impacts on job quality. We then lay out in detail a major research initiative on domestic outsourcing, discussing the questions it should answer and providing a menu of research methodologies and potential data sources. Such a research investment will be a critical resource for policymakers and other stakeholders as they seek solutions to problems arising from the changing nature of work.
Keywords: L24; L22; J31; 330; Outsourcing; subcontracting; independent contractors; staffing services; earnings inequality; job quality; data limitations; managerial theory